Indices of social knowledge in Italian-speaking children: Relations between personal pronouns, verb conjugations and mental state language. Issue 4 (August 2019) - Longobardi, Emiddia; Spataro, Pietro; Pecora, Giulia; Bellagamba, Francesca
This cross-sectional study investigated the use of four verbal indices of social knowledge (personal pronouns, verb conjugations, people words and mental state language) and their concurrent relations in a sample of 287 Italian-speaking children between 18 and 36 months. Results showed that the production of all indices increased with age. Mental state language (MSL) was positively associated to the use of personal pronouns and verb conjugations, suggesting that the difficulty in the acquisition of person-marking devices is partly due to social constraints. Moreover, both second- and third-person pronouns and verb conjugations were related to the acquisition of MSL, above and beyond the effects due to age and vocabulary. First-person references had no unique relation to MSL, after considering second- and third-person references. Lastly, the use of people words showed bidirectional associations with MSL, suggesting that the frequency of this category might be considered as an early verbal indicator of children's social knowledge.